Risk Factors for Acute Kidney Injury in ST-Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention - Yudi Putra; Budi Satrijo; Setyasih Anjarwani; Indra Prasetya; Anna Fuji Rahimah (Universitas Brawijaya, 2023)
BackgroundAcute kidney injury (AKI) is a frequent complication of ST-Elevation Myocardial Infarction (STEMI). AKI occurs in about 10% to 20% of patients with STEMI, which significantly impacts both short-term and long-term clinical outcomes.ObjectivesWe purposed to identify the risk factors for AKI among STEMI patients undergoing Primary PCI.MethodsThis retrospective cohort study analyzed 568 STEMI patients who underwent Primary PCI from 2017 to July 2022 at Saiful Anwar General Hospital Malang. We conducted both univariate and multivariate studies to determine AKI risk factors.ResultsThe risk factors for AKI among STEMI patients undergoing primary PCI were identified. The OR values for each were as follows: Shock condition (OR = 1.41; 95% CI = 1.18 – 1.92); Killip ≥3 (OR = 3.54; 95% CI = 2.14 – 4.26); and total contrast volume> 145 ml (OR = 1.61; 95% CI = 1.13 – 1.92). Based on the ROC curve analysis, total contrast volume >145 ml with an area under the curve (AUC) of 0.75 (95% CI = 0.65-0.85) with a specificity of 0.66 (95% CI = 0.61 – 0.71) and a sensitivity of 0.71 (95% CI = 0.65-0.76).ConclusionOur study revealed that the risk factors for AKI among STEMI patients undergoing primary PCI were shock condition, Killip class ≥3, and total contrast volume >145 ml.